An estimation of the evapotranspiration of typical steppe areas using Landsat images and the METRIC model. Issue 2 (30th December 2021) - Wang, Jun; Li, Heping; Lu, Haiyuan
Abstract: Remote sensing excels in estimating regional evapotranspiration (ET). However, most remote sensing energy balance models require researchers to subjectively extract the characteristic parameters of the dry and wet limits of the underlying surfaces. The regional ET accuracy is affected by wrong determined ideal pixels. This study used Landsat images and the METRIC model to evaluate the effects of different dry and wet pixel combinations on the ET in the typical steppe areas. The ET spatiotemporal changes of the different land cover types were discussed. The results show that the surface temperature and leaf area index could determine the dry and wet limits recognition schemes in grassland areas. The water vapor flux data of an eddy covariance system verified that the relative error between the ETd, METRIC and ETd, GES of eight DOYs (day of the year) was 18.8% on average. The ETMETRIC values of the crop growth season and the ETIMS of eight silage maize irrigation monitoring stations were found to have a relative error of 11.1% on average. The spatial distribution of the ET of the different land cover types in the study area was as follows: ETwater > ETarable land > ETforest land > ETunutilized land > ETgrassland > ETurban land . HIGHLIGHTS: Landsat images and the METRIC model estimating regional ET had obtained reliable and accurate results in typical steppe areas. The water vapor flux data of an eddy covariance system conducted the verification. The surface temperature and leaf area index could determine the dry and wet limits recognition schemes in grassland areas.